Pengaruh Literasi Akuntansi dan Penggunaan Aplikasi Keuangan terhadap Kualitas Pengelolaan Keuangan Generasi Z - Metyria Imelda Hutabarat; Pretty Naomi Sitompul; Rika Surianto Zalukhu (Politeknik Sawunggalih Aji, 2026)
The purpose of this study is to analyze the influence of accounting literacy and the use of financial applications on the quality of financial management among Generation Z in Medan City. This study uses quantitative research from primary data sources, with a questionnaire distribution technique for 93 respondents. Data analysis uses multiple linear regression analysis methods. Based on the results of this study, accounting literacy has a significant positive effect on the quality of financial management among Generation Z in Medan City. The use of financial applications has a significant positive effect on the quality of financial management among Generation Z in Medan City. The results of the Adjusted R Square study were 55.8%. While the remaining 44.2% were influenced by other variables outside this research model. The results of simultaneous research indicate that accounting literacy and the use of financial applications have a significant positive effect on the quality of financial management among Generation Z. Based on the results of this study, it is hoped that Generation Z can maintain the quality of financial management, improve accounting literacy and pay attention to the use of financial applications as needed so that the quality of financial management will improve.